L’enseignant Universitaire Algérien Face à L’enseignement Hybride - Khelef, Hanane; Khelef, Asma (جامعة الوادي - University of Eloued, 2022)
In front of a health crisis caused by the Covid19 pandemic, Algerian university teachers, like all teachers around the world, had to adapt very quickly to the measures of emergency taken by the government. New teaching methods have been considered by the Ministry of Higher Education in order to ensure pedagogical continuity. This contribution is intended is a study of one of these methods: Hybrid Education. It uses the results of an online questionnaire of a survey conducted among teachers. This questionnaire had as objective to identify the reality of Hybrid Education in Algeria. It focuses as well on its implementation in our university Echahid Hamma Lakhdar and consequently to identify the difficulties encountered by those teachers during the realization of their courses. Face à une crise sanitaire inédite provoquée par la pandémie du Covid 19, les enseignants universitaires algériens, comme tous les enseignants du monde, ont dû s’adapter très rapidement aux mesures d’urgences prises par le gouvernement. De nouvelles méthodes d’enseignement ont été envisagées par le ministère de l’enseignement supérieur afin d’assurer la continuité pédagogique. Cette contribution se veut une étude de l’une de ces méthodes : l’enseignement hybride. Elle exploite les résultats d’une enquête par questionnaire en ligne mené auprès des enseignants dont l’objectif est d’identifier la réalité de l’enseignement hybride en Algérie tout en menant une réflexion sur sa mise en œuvre dans notre université Echahid Hamma Lakhdhar et par conséquent, cerner les difficultés rencontrées par ces enseignants lors de la réalisation de leurs cours.
Réalité Et Perspectives
مقال
Keywords: Hybrid Education; University; University Teachers; Health crisis; Training Algeri; Enseignement hybride ; Université ; Enseignants universitaires ; Crise sanitaire ; Formation ; Algérie